Korupsi Kolektif (Korupsi Berjamaah) di Indonesia: Antara Faktor Penyebab dan Penegakan Hukum - Ridwan Arifin Oemara Syarief; Devanda Prastiyo (Jurnal Hukum Respublica, 2018)
The purpose of this study is to explain the factors that cause collective corruption in Indonesia. To achieve this goal, the research methods applied are normative research by comparing cases, laws and regulations, and theories related to collective corruption in Indonesia. The results of the study can be explained that the causes of corruption are due to individual and structural factors. Structural factors are supervision factors. The more effective the surveillance system is, the less chance of corruption. Conversely, if corruption is still widely practiced, it means something is wrong in the monitoring system, while what is meant by individual factors is the low level of morale and integrity of employees and leaders. So, if you pay attention, the Indonesian government is not a law and regulation that does not exist, but because of various factors that are outside the government structure, if the government controls corrupt people in any structure, that structure will definitely be tarnished.